Effektivnost' strelkovoi podgotovlennosti kvalifitsirovannykh biatlonistov - Shalaev, M. M.; Khrisanfov, G. N. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this study was to reveal the leading factors of the shooting preparedness, helping to improve the efficiency of elite biathlonners' competitive activity. The obtained data allowed to make an inference that the efficiency of the competitive activities as well as the high sports result in 10 km sprint race are determined by the rate of firing in the elite world biathloners and by the integral characteristics of technique (the total time of being in the firing line).